Obsessive and Harmonious Passion by Vallerand in The Fabelman (2022) - Junaedi, Difan (Universitas Negeri Surabaya, 2024)
This study aims to explore the transformation from obsessive to harmonious passion in the character of Sammy Fabelman in the film The Fabelmans (2022) using Vallerand's Dualistic Model of Passion (DMP). The primary objective is to understand Sammy's process of shifting from an obsessive and potentially detrimental passion to a harmonious and fulfilling one. A qualitative film analysis is conducted to identify critical moments and factors contributing to Sammy's transformation. The research findings indicate that Sammy transitions from compulsive and rigid involvement in his filmmaking activities to a more flexible, integrated engagement, positively impacting his psychological well-being. This study emphasizes the relevance and application of the DMP model in literary analysis and provides insights into the dynamics influencing changes in individual passion. The results are expected to contribute to understanding character development in literature and film and encourage further research to explore characters' passions comprehensively, bridging the gap between psychology and literature.Keywords: Passion, Dualistic Model of Passion, Obsessive, Harmonious, social-contextual